2017
DOI: 10.1252/jcej.16we350
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Scaling Up of Industrial Spray Dryers: A Review

Abstract: The paper presents a review of research works, experiments and simulations on spray drying in the industrial scale. The research area in the industrial spray drying process covers control of powder properties (bulk density, morphology), particles agglomeration ( nal PSD), residence time, wall deposition and safety of the process and the product. Limited number of literature references on spray drying in the industrial scale is due to high costs of running experiments and validation of theoretical models. Recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The protein contents were in the same range as in other studies [ 17 , 18 ]; however, other studies obtained higher protein yields (62–89%), probably attributed to the drying technique, as high losses are common during spray drying [ 38 ]. It is worth mentioning that protein isolation at industrial scale might result in higher yields when the drying kinetics are correctly determined [ 39 , 40 ]. The highest protein yield was 62.2 g protein kg −1 seed −1 obtained from the Orchestra cultivar, followed by Florida with 59.2 g kg −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The protein contents were in the same range as in other studies [ 17 , 18 ]; however, other studies obtained higher protein yields (62–89%), probably attributed to the drying technique, as high losses are common during spray drying [ 38 ]. It is worth mentioning that protein isolation at industrial scale might result in higher yields when the drying kinetics are correctly determined [ 39 , 40 ]. The highest protein yield was 62.2 g protein kg −1 seed −1 obtained from the Orchestra cultivar, followed by Florida with 59.2 g kg −1 .…”
Section: Resultsmentioning
confidence: 99%
“…For sure, there are limitations in applying this model, such as the inability to predict potential hot or cold spots that may form inside the spray dryer that can further degrade the phenolic compounds thus reducing the quality of the encapsulated product. The prediction of hot and cold spots can be made through the use of computational fluid dynamics (CFD) models (Zbicinski et al, 2017). These models give in-deep information and are very useful for the design of the equipment, but, on the contrary, are not very suitable for optimization of operating conditions due to the high computational effort required.…”
Section: Modeling Of Spray-drying Process For Barbera Extractsmentioning
confidence: 99%
“…This is largely due to the fact that spray drying involves a combination of complex physical transformations that include the mixing of the main dried component and excipients in a suitable solvent, liquid atomization, solvent evaporation (drying), gas-particle separation, and often secondary drying, which may take place in a fluidized bed dryer [16]. Scale-up studies of spray dryers (particularly in the field of pharmaceutical drying) can be found in the literature and include specific process scalingup design procedures [15][16][17][18][19][20][21]. However, the limited number of literature reports on industrial scale spray drying is due to the high cost of conducting such experiments and validating theoretical models [21].…”
Section: Introductionmentioning
confidence: 99%
“…Scale-up studies of spray dryers (particularly in the field of pharmaceutical drying) can be found in the literature and include specific process scalingup design procedures [15][16][17][18][19][20][21]. However, the limited number of literature reports on industrial scale spray drying is due to the high cost of conducting such experiments and validating theoretical models [21].…”
Section: Introductionmentioning
confidence: 99%